2014
DOI: 10.1097/01.mib.0000440984.86659.4f
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anti–Tumor Necrosis Factor Alpha Antibodies Administered to Pregnant Women With Inflammatory Bowel Disease on Long-term Outcome of Exposed Children

Abstract: Exposure to anti-TNF-α antibodies seems to be safe for growth and psychomotor development of children, although clinical significance of relatively high frequency of infections and antibiotic use among infants remains questionable because of the lack of a control group. Continuous follow-up of exposed children is absolutely warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 13 publications
3
69
0
4
Order By: Relevance
“…There are limited data available on the long-term outcomes of children born to mothers exposed to anti-TNFα during pregnancy. Some studies have suggested that there are no adverse effects on childhood development; 99,100 however, further research to discern the risk of anti-TNFα on long-term outcomes is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited data available on the long-term outcomes of children born to mothers exposed to anti-TNFα during pregnancy. Some studies have suggested that there are no adverse effects on childhood development; 99,100 however, further research to discern the risk of anti-TNFα on long-term outcomes is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…64 However, another study reported 15 children exposed to anti-TNF in utero who had no serious complications after bacille Calmette-Guérin vaccination within 1 week of birth. 65 Immunologic development also was evaluated, and 17 children tested had normal cellular immunity. All children had detectable serologic response to vaccinations.…”
Section: Cyclosporinementioning
confidence: 99%
“…On the other hand, there are conflicting data on higher infection rates among offspring. While observational studies found no increased risk [18][19][20] , PIANO registry [17] reported a significant rise in infections at 12 months of age of infants exposed to the combination therapy compared to the unexposed group.…”
Section: Discussionmentioning
confidence: 99%